PENGARUH DETERMINAN FRAUD HEXAGON THEORY DALAM MENDETEKSI FRAUDULENT FINANCIAL STATEMENT - Puspitasari, Hana Pradipta; Harto, Puji (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2024)
Financial statement fraud is a problem that often occurs and causes many losses. Although the proportion is lower than that of corruption and misuse of assets, the impact of the losses caused is the greatest. This study uses the F-Score model measurement to examine the effect of the determinants of fraud hexagon theory in detecting fraudulent financial statements. Tests were conducted on the Jakarta Islamic Index (JII) for the 2018-2022 period, with a sample of 55 selected through purposive sampling. Data analysis using multiple linear regression analysis. The results showed that changes in auditors significantly negatively affect fraudulent financial statements. In contrast, financial stability, ineffective monitoring, change in director, frequent number of CEO's pictures, and government projects do not affect fraudulent financial statements. The results of this study provide implications for users of financial statements in identifying the factors that cause fraud so that they can prepare effective strategies to detect and prevent fraud.